A rapid and effective method for silver staining of PCR products separated in polyacrylamide gels. Issue 17 (18th June 2014) - Liang, Qingzhi; Wen, Dingqing; Xie, Jianghui; Liu, Liqin; Wei, Yongzan; Wang, Yicheng; Shi, Shengyou
<x xml:space="preserve">Abstract</x> With the development of molecular quantitative genetics, particularly, genetic linkage map construction, quantitative trait loci mapping or genes fine mapping and association analysis etc., more and more PCR products separated in polyacrylamide gels need to be silver‐stained. However, conventional silver‐staining procedures are complicated and time‐consuming as they require a lot of preparation and handling of several solutions prior to use. In this study, a simple and rapid protocol for silver staining of PCR products was developed. The number of steps was reduced compared to conventional protocols, thus achieving detection of PCR products in 7 min, saving time and resources. Fixation and staining solution and developing solution in present staining procedure allowed a reutilization for 12 and 8 times, respectively, reducing the cost greatly. Meanwhile, the sensitivity was significantly improved with the improved method and the minimum of 0.097 ng/μL of DNA amount can be detected in denaturing polyacrylamide gel. The protocol developed in this study will facilitate the development of molecular quantitative genetics.